A DIC method to determine the Mode I energy release rate G, the J-integral and the traction-separation law simultaneously for adhesive joints. (July 2020) - Sun, F.; Blackman, B.R.K.
Highlights: DIC is used to characterize the Mode I fracture of adhesive joints. A novel DIC based method is proposed to measure the crack length during fracture. The J -integral and G are measured and compared to analyse the validity of LEFM. The TSLs of adhesive joints are deduced and evaluated by FE modelling. Abstract: The quasi-static Mode I fracture behaviour of joints bonded with either a brittle or toughened epoxy adhesive or a ductile polyurethane adhesive has been investigated by means of digital image correlation (DIC). A novel method to measure the crack length using DIC analysis is proposed. By measuring the crack tip separation, beam rotation and crack length, the energy release rate G and the J -integral are obtained and are compared to analyse the validity of Linear Elastic Fracture Mechanics (LEFM) methods. Simultaneously the traction-separation laws (TSLs) for the adhesive joints were measured. The TSLs were then used as input data for FE modelling to evaluate their accuracy by comparing with experimental results. It is shown that LEFM is valid for the joints bonded with either the brittle or toughened epoxy adhesives but is invalid for joints bonded with the polyurethane adhesive. The procedure proposed here to measure the crack length via DIC shows great promise and can be automated readily in practice.